Integration of solar technology into the electric railway system in dense urban regions - Ahmed Mohamed; Rohama Ahmad; Bonny Xavier (IET Smart Grid)
Abstract This paper investigates the deployment of solar technology throughout an electric railway system to accommodate tractive power needs. The approach is evaluated from both a technical and financial standpoint to better understand its overall feasibility. A case study is presented using New York City's subway system as the centre of deployment. As a means to both prevent excess voltages, as well as contribute to the city's shift to zero emission, parallel electric bus charging is also studied. It has been demonstrated that the proposed integration allows the subway system to still function without any hindrance to rail operation. The system is able to provide charging power for three to six electric buses per passenger station. In addition, the approach shows long‐term financial growth with average annual electric bill savings of approximately $50,000 per passenger station, each with a relatively short payback period of approximately 4 years.